Wind relaxation and a coastal buoyant plume north of Pt. Conception, CA: Observations, simulations, and scalings. Issue 10 (13th October 2016) - Suanda, Sutara H.; Kumar, Nirnimesh; Miller, Arthur J.; Di Lorenzo, Emanuele; Haas, Kevin; Cai, Donghua; Edwards, Christopher A.; Washburn, Libe; Fewings, Melanie R.; Torres, Rachel; Feddersen, Falk
Abstract: In upwelling regions, wind relaxations lead to poleward propagating warm water plumes that are important to coastal ecosystems. The coastal ocean response to wind relaxation around Pt. Conception, CA is simulated with a Regional Ocean Model (ROMS) forced by realistic surface and lateral boundary conditions including tidal processes. The model reproduces well the statistics of observed subtidal water column temperature and velocity at both outer and inner‐shelf mooring locations throughout the study. A poleward‐propagating plume of Southern California Bight water that increases shelf water temperatures by ≈ 5°C is also reproduced. Modeled plume propagation speed, spatial scales, and flow structure are consistent with a theoretical scaling for coastal buoyant plumes with both surface‐trapped and slope‐controlled dynamics. Plume momentum balances are distinct between the offshore (>30 m depth) region where the plume is surface‐trapped, and onshore of the 30 m isobath (within 5 km from shore) where the plume water mass extends to the bottom and is slope controlled. In the onshore region, bottom stress is important in the alongshore momentum equation and generates vertical vorticity that is an order of magnitude larger than the vorticity in the plume core. Numerical experiments without tidal forcing show that modeled surface temperatures are biased 0.5°C high, potentially affecting plume propagation distance and persistence. Key Points: A multinested model reproduces the temperature and current variability at outer and inner‐shelf sites around Pt. Conception Consistent with observations, the modeled response to wind relaxation is a poleward‐propagating, coastally trapped, buoyant plume The model resolves well the differences between offshore and onshore plume dynamics